Democratic Republic of Timor-Leste : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
Petroleum is now by far Timor-Leste's largest source of income. If well harnessed, Timor-Leste's petroleum wealth offers the potential for a more prosperous future. This Selected Issues paper provides an overview of how Timor-Leste's Petroleum Fund functions. It considers the extent of the country's petroleum wealth, discusses the developmental challenges, and outlines key challenges ahead. The paper depicts the origins of the fund and details its operating mechanisms. It also assesses how the fund has performed to date.